Vulnerabilidad en el empleo, género y etnicidad en el Perú - Garavito, Cecilia (2010)
The objective of this research is to analyze the vulnerability in employment of urban labor force,by ethnicity and by sex, for the period 2004-2006. We define vulnerability in employment as theprobability that the labor market status of a worker worsens regarding his past situation. By meansof the ENAHO (INEI) panel urban data for 2004-2006, we find that women, young people, workers older than 45 years old, and those with less education are most vulnerable to leaving thelabor force, or to losing the quality of their job. Education of good quality is important to reducethese vulnerabilities.